(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2018)
Abstract: This issue presents a literature review on Educational Policy in Brazil in the period from 1994 to 2018. The analysis performed takes the Social Theory by Pierre Bourdieu as basis, which considers the knowledge production as part of the symbolic production in a specific field. From this literature review, it is indicated that Educational Policy is discussed, in Brazil, as research object, a subject that belongs to the Policy Science, theoretical study field, but predominantly as an academic field. The works analyzed show that: a) the research subjects of Educational academic field are focused on actions and omissions by the State; b) the authors point to there are challenges for the Educational Policy research; c) the main gaps are regard to the need for deepening the discussion on the study subjects of Educational Policy, greater deepening of analysis and explanations of theoretical-epistemological perspectives used. Keywords: Educational Policy. Academic field. Literature review.